A gene-base DBMS - Noori, Hadeel; A., Hanan; A., Wegdan (Journal of Al-Qadisiyah for Computer Science and Mathematics, 2017)
The task of the query optimizer is to accept as input a tree of relational algebra operators and to produce a query execution plan. This plan specifies exactly which operations should be performed, in which order. Algebra space can express the solution space, whereas a good search algorithm can finding an optimal solution. In this work a genetic algorithm with two crossover strategies will be tested on a B+ tree sorted database example and nested loop join strategy. The results show that using M2S crossover with left-deep strategy will give better solutions.